PP.20.10: INTERRELATIONSHIP BETWEEN BRACHIAL-ANKLE AND CAROTID-FEMORAL PULSE WAVE VELOCITY AND THEIR ASSOCIATIONS WITH CARDIOVASCULAR RISK FACTORS AND TARGET ORGAN DAMAGE. (June 2015) - Cheng, Y.B.; Li, Y.; Zhang, Y.; Li, L.H.; Sheng, C.S.; Huang, Q.F.; Wang, J.G.
Abstract : Objective: Carotid-femoral pulse wave velocity (cfPWV) is currently the standard measure of aortic stiffness. Brachial-ankle PWV (baPWV) can be more conveniently measured with an oscillometric cuff technique. We investigated the interrelationship between baPWV and cfPWV and their associations with cardiovascular risk factors and target organ damage. Design and method: Our study was conducted in the framework of comprehensive cardiovascular examinations in a workplace population living in a coast area, 300 kilometers south of Shanghai. BaPWV and cfPWV was measured using the Colin VP1000 (OMRON, Japan) and SphygmoCor (AtCor, Australia) devices, respectively. Mean intima-media thickness (IMT) at the right carotid artery was determined by an echotracking system (Esaote, Italy). Echocardiography was performed with a Mylab 30 CV machine (Esaote, Italy). Pearson's correlation and single and multiple regressions were applied for analyses. Results: The 954 participants (630 [66.0%] men, mean [±standard deviation] age 42.6 ± 14.2 years) included 203 (21.3%) hypertensive patients, of whom 89 (9.4%) took antihypertensive medication. BaPWV and cfPWV averaged 13.4 ± 2.7 and 7.3 ± 1.6 m/s, respectively. In unadjusted analysis, baPWV was significantly (P < 0.001) associated with cfPWV in all subjects (r = 0.75) and in men (r = 0.72) and women (r = 0.80). BaPWV and cfPWV shared similar major determinants, such as age (both partial r2 = 0.11) and systolic blood pressure (partial r2 = 0.51 and 0.44 for baPWV and cfPWV respectively). BaPWV and cfPWV were significantly (P < 0.001) and similarly (P > 0.29) associated with carotid IMT (r = 0.53 and 0.50, respectively), left ventricular mass index (r = 0.19 and 0.15), E/A ratio (r = -0.56 and -0.53) and deceleration time of E velocity (DTE, r = 0.43 and 0.39). After adjustment for other common cardiovascular risk factors, all above associations became non-significant (P > 0.15), except for both PWVs with DTE (partial r2 = 0.19 and 0.16, P < 0.02). Conclusions: BaPWV and cfPWV were closely correlated, and had similar major determinants and associations with cardiovascular target organ damage, indicating that baPWV can be an alternative measure of arterial stiffness and surrogate of cardiovascular damage.